INFLUENCE OF ENGINEERING PROPERTIES OF SOILAND GROUNDWATER MOVEMENT ON GULLY DEVELOPMENT IN RAFINGORA, NORTHERN BIDA BASIN, NIGERIA - Omeiza, Muhammed Nurudeen; Idris-Nda, Abdullahi; Waziri, Salome Hephziba; Waziri, Nuhu (FUDMA Journal of Sciences, 2022)
The formation and expansion of gullies in Rafingora community, northern sector of the Bida Basin, Nigeria was investigated. This was aimed at determining the controlling factors for gully development in the area, using field gully parameter measurements, hydrogeological mapping and geotechnical investigation of soils from gully sites. U-shaped gullies were mapped with sliding, slumping and block fracturing as the main modes of gully propagation. Relief is gentle; slope angles range from 1.58° to 1.96°, indicating little or no influence of elevation on gully development. Gullies were found to be deeper than 3m, with drainage area of more than 30m. Depth to water in open wells ranges from 5.5m in the north-eastern part to about 16.4m in the south-western part. Gullies in the north-eastern side are mostly shallower than the water table, contrary to the situation in the south-western part. This shows a direct relationship between water table elevation and gully propagation and is further exacerbated by the relatively high average hydraulic of soils.  The soils have low plasticity, cohesion, angle of internal friction (AIR) and maximum dry density (MDD). A combination of these poor geotechnical properties makes the soils friable and crumbles easily when in contact with water and offers very little resistance to erosion. Conclusively, gully development in Rafingora is influenced more by bottom erosion due to high hydraulic conductivity and seepage forces, rather than by overland runoff. Reclamation attempts may consider lowering groundwater levels as a major strategy for erosion control in the area.
Keywords: Bida Basin; Gully Erosion; Soil properties; Groundwater; Geo-hazards